1997
DOI: 10.1111/j.1440-1738.1997.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Miocene intra‐arc bending at an arc‐arc collision zone, central Japan

Abstract: Recent paleomagnetic studies are reviewed in an effort to clarify the relationship between the intra-arc deformation of central Japan and the collision tectonics of the Izu-Bonin Arc. The cusp structure of the pre-Neogene terranes of central Japan, called the Kanto Syntaxis, suggests a collisional origin with the Izu-Bonin Arc. The paleomagnetic results and newly obtained radiometric ages of the Kanto Mountains revealed the Miocene rotational history of the east wing of the Kanto Syntaxis. More than 90" clockw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 45 publications
(19 reference statements)
2
89
0
2
Order By: Relevance
“…1) (Taira et al, 1989;Soh et al, 1991). The collision of the IBM arc to the Honshu arc led to northward bending of the pre Neogene accreted terranes of the Honshu arc (Kanto Syntaxis) (Takahashi and Saito, 1997). The Izu collision zone provides a unique opportunity to examine the terrane accretion processes and the structure of the northern Izu arc crust.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…1) (Taira et al, 1989;Soh et al, 1991). The collision of the IBM arc to the Honshu arc led to northward bending of the pre Neogene accreted terranes of the Honshu arc (Kanto Syntaxis) (Takahashi and Saito, 1997). The Izu collision zone provides a unique opportunity to examine the terrane accretion processes and the structure of the northern Izu arc crust.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The Izu collision zone provides a unique opportunity to examine the terrane accretion processes and the structure of the northern Izu arc crust. Collision of the northern IBM arc with central Honshu has been occurring since the mid Miocene ( 15 Ma) (Niituma, 1989;Soh et al, 1991;Takahashi and Saito, 1997;Aoike, 1999). The collision has led to the accretion of the Izu Bonin arc crust onto the Honshu arc, associated with the sequential southward migration of the plate boundary and trench (Soh et al, 1991;Taira et al, 1998).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…, Takahashi and Saito, 1997;, 1999;Otofuji et al, 19991980Itoh, 1986, 1988Hyodo and Niistuma, 1986;Takahashi and Nomura, 1989;, 1992;Takahashi and Watanabe, 1993;Hayashida, 1994;Takahashi and Saito, 1997;Otofuji et al, 1999;Itoh et al, 2006 MTL 80 Niitsuma andAkiba, 1985;Niitsuma and Matsuda, 1985;Hyodo and Niitsuma, 1986;Niistuma, 1989 6 Ma MTL Niitsuma, 1989 Takahashi and Saito 1997 Hyodo and Niitsuma, 1986;Takahashi and Watanabe, 1993 16 Ma 6 Ma (Hayashida and Ito, 1984); 2 = lower part of the Morozaki Group (Hayashida, 1986); 3 = Kani Group (Hayashida et al, 1991); 4 = Mizunami Group ; 5 = Hokusetsu Subgroup (Torii, 1983); 6 = Tomikusa Group (Hayashida, 1992); 7 = Kurami and Saigo groups (Hayashida, 1994); 8 = Chichibu basin sediments (Hyodo and Niitsuma, 1986). Accreted volcano-sedimentary units (Amano et al, 1999;Aoike, 1999) that initially formed on the Izu-Bonin Arc are also shown: K = Kushigatayama or Koma unit; M = Misaka unit.…”
mentioning
confidence: 99%
“…Petrogenesis of the Izu Collision Zone granitoid plutons together with other oceanic arc collision related magmatism collectively suggest that collision has played an important role in transforming juvenile oceanic arc into mature continental crust. Takahashi and Saito, 1997;Saito et al, 2004Saito et al, , 2007aSaito et al, , 2007bSaito et al, , 2012 (Condie, 1993;Gao et al, 1998;Borodin, 1998;Wedepohl, 1995;Rudnick and Gao, 2003) . SiO 2 versus SrI (at zircon U Pb age) of the rocks of the Tanzawa plutonic complex (Kawate, 1996) (a), the Kofu granitic complex (b), and the Kaikomagatake pluton (c).…”
Section: 齊藤mentioning
confidence: 99%